PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENURUNAN PERILAKU AGRESIF SISWA KELAS XI AK/ADP SMK TELKOM PEKANBARU T.P 2015/2016 - Dina Yunita; Raja Arlizon; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The causes of aggressive behavior done by students are complicated,however, it can be divided into two groups, namely, internal and external causes such as anger,frustration, environment, violent model of learning process, erroneously discipline process. Theboth factors cause inhibiting in the development of students’ emotional and social aspects. Theinhibiting in the development of students’ emotional and social aspects is showed by doingaggressive behavior. It influences the development of students’ emotion and behavior at school.The aim of this study is to obtain the impact of group guidance and counseling services to thedecreasing of the aggressive behavior of students grade XI AK/ADP SMK Telkom Pekanbaru,academic year 2015/2016. This study was carried out at SMK Telkom Pekanbaru fromFebruary 2016 to May 2016. The method used in this study is experimental method by using thepattern of pretest and post test control group design. The subject of this study is the studentswho undergo the problems of the high aggressive behaviors. The technique of data analysisuses three formula, namely Wilcoxon Experiment, Spearman Rank Experiment and ManWhitney Experiment. Based on the hypothesis experiment by applying SPSS 16.0, it is obtainedthat the value of sig. (2-tailed) is 0.025. Due to the fact that the value of sig. (2-tailed) fewerthan the α value (0.025 < 0.05) thus it can be concluded that There is positive impact thatsignificant in giving group counseling services in the decreasing of students’ aggressivebehavior give medium contribution, that is 48,5 %.Keywords: group guidance services, aggressive behavior